Netizen Sentiment And Innovative Attributes In Halal Skincare Markets - Wanda Khairun Nasirin; M. Fauzan; Deis Fatma Fauziah; Rizki Mulia Lubis (Riset Anak Bangsa, 2025)
Netizens can provide valuable insights into consumer responses to innovative attributes in halal skincare product lines, but it is undeniable that emerging sentiments about beauty standards can be detrimental to halal skincare products. This study evaluates netizens' responses to innovative attributes in halal skincare products and examines the moderating effect of beauty standards. The research method used includes sentiment analysis, systematic literature review, and SEM-PLS by collecting data via Twitter and the Orange Data Mining application. The results of the study show that the innovative attributes variable has a positive and significant influence on the behavior of netizens in halal skincare. Netizens show a positive response to innovation in halal skincare products. However, the moderating effect of beauty standards shows that beauty standards have a negative influence on the relationship between innovative attributes and netizen behavior. This indicates that the level of beauty standards held by netizens can influence the way they respond to innovations in halal skincare products. These findings have practical implications for halal skincare companies in designing effective marketing strategies. Companies need to consider the importance of innovation in their products while understanding the influence and expectations of consumer beauty standards. By strengthening innovation by existing beauty standards, companies can build a positive image, increase consumer satisfaction, and maintain a competitive advantage in the halal skincare market.